(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the prevalence of erectile dysfunction and identify associated factors following radical cystectomy for bladder cancer. Methods: A prospective longitudinal study was conducted on 117 male patients undergoing radical cystectomy at Binh Dan Hospital (from November 2020 to November 2024). Erectile function was assessed using the IIEF-5 score before surgery and at 3 months, 6 months, 12 months postoperatively. Results: The patients had a mean age of 60.1 ± 9.6 years. The mean preoperative IIEF-5 score was 17.14, with 32.5% having normal erectile function. Postoperatively, mean IIEF-5 scores declined to 6.0, 6.5, and 11.35 points at 3 months, 6 months, and 12 months, respectively. At 3 months, all patients had severe erectile dysfunction; no patient recovered to normal function at 12 months. Preoperative IIEF-5 score was the only independent predictor (β = 0.32; 95% CI: 0.23-0.41; p < 0.001). Conclusion: Erectile dysfunction is a common complication following radical cystectomy, with significant decline and limited recovery at 12 months. Preoperative sexual function assessment, nerve-sparing techniques when oncologically appropriate, and postoperative penile rehabilitation should be integrated into long-term patient care.